Will We Ever Have Conscious Machines? - Krauss, Patrick; Maier, Andreas (Frontiers in Computational Neuroscience, 2020)
The question of whether artificial beings or machines could become self-aware or consciousness has been a philosophical question for centuries. The main problem is that self-awareness cannot be observed from an outside perspective and the distinction of being really self-aware or merely a clever imitation cannot be answered without access to knowledge about the mechanism's inner workings. We investigate common machine learning approaches with respect to their potential ability to become self-aware. We realize that many important algorithmic steps towards machines with a core consciousness have already been taken.